1988
DOI: 10.1104/pp.86.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Nitrogen Assimilation in Cowpea Nodules Studied using 15N2 and Allopurinol

Abstract: In the presence of 0.5 millimolar aliopurinol (4-hydroxypyrazolo 13,4-dipyrimidine), an inhibitor of NAD:xanthine oxidoreductase (EC 1.23.2), intact attached nodules of cowpea ( Vigna unguiculata L. Walp. cv Vita 3) formed ['5Nlxanthine from 15N2 at rates equivalent to those of ureide synthesis, confirming the direct assimilation of fixed nitrogen into purines. Xanthine accumulated in nodules and was exported in increasing amounts in xylem of allopurinol-treated plants. Other intermediates of purine oxidation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…The ureides are translocated in xylem to the host and constitute the major source of N for plant growth. Studies based on the use of stable and radioactive isotopes (Atkins et al, 1982(Atkins et al, , 1988, on the application of specific metabolic inhibitors (Fujihara and Yamaguchi, 1978;Atkins et al, 1980), and on the isolation and characterization of critical enzymes (Atkins, 1991) have established the broad features of the metabolic pathway of ureide synthesis. Ammonia is assimilated in the infected plant cell by Gln synthetase and GOGAT, providing both amide and amino-N to de novo purine synthesis.…”
mentioning
confidence: 99%
“…The ureides are translocated in xylem to the host and constitute the major source of N for plant growth. Studies based on the use of stable and radioactive isotopes (Atkins et al, 1982(Atkins et al, , 1988, on the application of specific metabolic inhibitors (Fujihara and Yamaguchi, 1978;Atkins et al, 1980), and on the isolation and characterization of critical enzymes (Atkins, 1991) have established the broad features of the metabolic pathway of ureide synthesis. Ammonia is assimilated in the infected plant cell by Gln synthetase and GOGAT, providing both amide and amino-N to de novo purine synthesis.…”
mentioning
confidence: 99%
“…Xanthine dehydrogenase (XDH; EC 1.1.1.204) is an essential enzyme in'the biogenesis ofthe ureides allantoin and allantoic acid in cowpea and soybean nodules (1)(2)(3). The production of ureides in nodules is correlated with N2 fixation in tropical legumes ofthe tribe Phaseoleae, where up to 90% ofthe fixed nitrogen is assimilated in nodules in ureide form (4).…”
mentioning
confidence: 99%
“…It is possible, therefore, that the 15 N present in the amino acids was not assimilated in the nodule, but in a different location and some of these labelled amino acids translocated to the nodule. In this respect, it is pertinent to observe that in other studies it was suggested that at least part of the Asn of the nodule came from a different source and not from assimilation in the nodule itself (Atkins et al 1988(Atkins et al , 1990.…”
Section: Discussionmentioning
confidence: 99%